Template-free preparation of anthracite-based nitrogen-doped porous carbons for high-performance supercapacitors and efficient electrocatalysts for the oxygen reduction reaction. Issue 42 (6th August 2019) - Qi, Jiawei; Jin, Bolin; Bai, Peiyao; Zhang, Wendu; Xu, Lang
Abstract : Acting as supercapacitor electrodes and ORR electrocatalysts, anthracite-based nitrogen-doped porous carbons are prepared by one/two-step activation/doping processes. Abstract : The conversion of coal into high-performance electrochemical energy materials, exemplified by electrodes and electrocatalysts for supercapacitors and fuel cells, is currently crucial to the advancement of high value-added, clean and non-fuel utilization of coal resources. In this work, anthracite-based nitrogen-doped porous carbon (ANPC) materials with well-defined pore architectures and adjustable nitrogen concentrations were prepared without any template: ANPC-1 by a one-step activation/doping process and ANPC-2 by a two-step process. The specific capacitance value of the ANPC-1 materials could attain a maximum of 346.0 F g −1 at the current density of 0.5 A g −1 in 6 M KOH. Supercapacitors composed of the ANPC-1 electrodes were able to achieve high energy densities up to 10.3 W h kg −1 and 20.8 W h kg −1, together with good charge/discharge stabilities of 95.4% and 91.3% after 5000 cycles, in KOH and Na2 SO4 aqueous electrolytes, respectively. The ANPC-2 materials are more associated with the oxygen reduction reaction (ORR): one possessed a comparable ORR electrocatalytic activity to the commercial JM Pt/C (20% Pt) catalyst, and, moreover, its onset potential (0.96 V vs. RHE), half-wave potential (0.85 V vs. RHE), catalyst durability (95.9% activity retained after 40 000 s) and methanol tolerance were all superior to the benchmark electrocatalyst. This study provides a feasible route to rational design of coal-based multifunctional materials towards electrochemical energy storage and conversion.